Implementation Of Genetic Algorithm In Determining Point Of Connecting Power Supply For Beautiful Kiat Pulp And Paper (Ikkp) Substations To Gemini Feeder Substation Perawang Pt. Pln (Persero) Perawang Customer Service Unit - Zulfahri,; Abrar Tanjung2,; Monice, (Human Sustainability Procedia, 2021)
Increasing power demand and high load density makes power system operation more complicated. In the distribution of electricity to consumers that are located far apart, the system experiences an increase in power losses and a large voltage drop which results in low performance of the system. To achieve the goal of distributing electrical energy to the load by minimizing power losses and delivering quality electrical energy, a connection point is made to load from the feeder overloaded to the underloaded feeder. One of the Perawang GI feeders, the Gemini feeder, supplies electricity to the Mandau River sub-district, which is a distance of more than 100 km from the GI Perawang, causing a voltage drop and PT. PLN (Persero) Perawang ULP. Then determine the connection point of the system that aims to reduce losses, increase stability, increase the voltage profile through the Genetic Algorithm method found 3 possible connection points. The results of the proposed method, the existing condition found a voltage of 20.08 kV and power losses of 48 kW. After optimization found an optimal connecting point between Gemini feeder and GH IKPP, namely Recloser Inpress Bunut in Normaly Open (NO) with a voltage value of 19, 4 kV and distribution losses of 21 kW.